Primary leptomeningeal T-cell lymphoblastic lymphoma: a rare cause of chronic meningitis - Elavarasi, Arunmozhimaran (BMJ Case Rep, 2020)
Primary leptomeningeal lymphomatosis is a rare disease with only a few hundred cases reported. We present a patient with a relatively short history of 25 days of headache followed by diplopia who was found to have primary leptomeningeal T-cell lymphoma without evidence of systemic lymphoma. The patient responded well to chemotherapy along with intrathecal medication and cranial irradiation and returned to a completely normal state of health. Not all chronic meningitis is due to infection or self-limiting inflammatory causes. It is important to consider lymphoma as a differential even in the absence of constitutional features such as loss of weight, appetite, night sweats, lymphadenopathy or hepatosplenomegaly. T-cell lymphoma with only Central Nervous system (CNS) involvement is a rare cause of chronic meningitis, which is eminently amenable to treatment and is fatal if missed.